Interspecific competition between Metagonystilum minense (Diptera: Tachinidae) and Cotesia flavipes (Hymenotera: Braconidae) parasitoids of sugarcane borers (Diatraea spp., Lepidoptera:Pyralidae) - Weir L., Enrique H (1998)
We evalualed the effect of interspecific competition between M. minense and C. flavipes larvae on survival in both species and on the growth of M. minense. Interspecific competition was evaluated by the inoculation of M. minense larvae (l or 2 per host larvae: D. sachara lis) I to 5 days before or 3 to 8 days after the inoculatíon of C.flavipes eggs (one inoculation = 45 - 50 eggs). AH experiments were done with ten replicas. We found a significant effect of ínterspecific competition on larval and pupal survival in both parasitoids and body weight in M. minense. M. minense dominated over C. flavipes, except when M. minense was inoculated 5 or more days after C. flavipes.